Perkembangan Hukum dan Kejahatan Siber “Cybercrime” di Indonesia - Mohamad Revaldy Fairuzzen; Abil Arya Putra; Akmal Reihan; Lilik Prihatini S.H, M.H (Sharia Journal and Education Center Publishing, 2024)
Abstract: Technological progress and its implementation have always had a wide impact, both in the context of social life, the development of the business world, and in the evolution of Moral, Ethical, and Legal values. Various technologies are considered to have the potential to fundamentally change the paradigm of global life. The growth of multimedia technology, for example, has resulted in significant developments in the field of telecommunications. This includes not only developments in basic communications, but also involves additional technologies that provide more value. Large penetration of the Internet, if not managed wisely, can lead to the emergence of cybercrime, known as cybercrime or cybercrime, which is a further development of computer crime. Criminal offenses in the realm of information technology are a relatively recent phenomenon, especially when compared to conventional crimes. Information technology crime arose along with the information technology revolution and increasingly physically minimal social interaction, being one of the hallmarks of that revolution. The fight against cybercrime by law enforcement is strongly influenced by the existence of legal regulations. There are several legislations related to information technology, in particular crimes related to the internet, which are regulated in national regulations. Keywords: Cybercrime, Technology, Development Abstrak: Kemajuan teknologi beserta implementasinya selalu memiliki dampak yang luas, baik dalam konteks kehidupan sosial, perkembangan dunia bisnis, maupun dalam evolusi nilai-nilai Moral, Etika, dan Hukum. Berbagai teknologi dianggap memiliki potensi untuk mengubah paradigma kehidupan global secara menyeluruh. Pertumbuhan teknologi multimedia, misalnya, telah menghasilkan perkembangan yang signifikan dalam bidang telekomunikasi. Ini tidak hanya mencakup perkembangan dalam komunikasi dasar, tetapi juga melibatkan teknologi tambahan yang memberikan nilai lebih. Penetrasi internet yang besar, jika tidak dikelola dengan bijak, dapat menyebabkan timbulnya kejahatan di dunia maya, dikenal sebagai kejahatan siber atau cyber crime, yang merupakan perkembangan lebih lanjut dari kejahatan komputer. Tindak pidana dalam ranah teknologi informasi merupakan fenomena relatif baru, terutama jika dibandingkan dengan kejahatan konvensional. Kejahatan teknologi informasi muncul seiring dengan revolusi teknologi informasi dan interaksi sosial yang semakin minim secara fisik, menjadi salah satu ciri khas revolusi tersebut. Penanggulangan kejahatan siber oleh penegak hukum sangat dipengaruhi oleh adanya regulasi hukum. Ada beberapa perundang-undangan yang terkait dengan teknologi informasi, khususnya kejahatan yang terkait dengan internet, yang diatur dalam peraturan nasional. Kata kunci: Cybercrime, Teknologi, Perkembangan